Wedding date in Malaysia - Douglas, Michelle (Harlequin Enterprises ULC, 2022)
"Bridesmaid Ella wants to prove she's moved on from the grief of the last eighteen months and is ready for a fresh start. So meeting playboy and best man Harry at the wedding party in Malaysia is excitingly refreshing! With an image to redeem, Harry's solely focused on making the wedding perfect and he needs Ella's help. But when their best-laid plans are derailed by their unstoppable chemistry, keeping focused becomes almost impossible."--back cover.